"Be Nice or Leave Me Alone": An Intergroup Perspective on Affective Polarization in Online Political Discussions. (April 2022) - Marchal, Nahema
Affective polarization—growing animosity and hostility between political rivals—has become increasingly characteristic of Western politics. While this phenomenon is well-documented through surveys, few studies investigate whether and how it manifests in the digital context, and what mechanisms underpin it. Drawing on social identity and intergroup theories, this study employs computational methods to explore to what extent political discussions on Reddit's r/politics are affectively polarized, and what communicative factors shape these affective biases. Results show that interactions between ideologically opposed users were significantly more negative than like-minded ones. These interactions were also more likely to be cut short than sustained if one user referred negatively to the other's political in-group. Conversely, crosscutting interactions in which one of the users expressed positive sentiment toward the out-group were more likely to attract a positive than a negative response, thus mitigating intergroup affective bias. Implications for the study of online political communication dynamics are discussed.